Pasantía en apoyo a la empresa Sygemin S.A.S. para el desempeño de conocimientos adquiridos - Diaz Amézquita, Cristian Santiago (Universidad Antonio Nariño, 2022)
The company Services and mining management Sygemin S.A.S, located in the municipality of Duitama in the Department of Boyacá, is dedicated to the provision of services, focused on three work fronts such as: areas focused on environmental issues, mining planning, safety and health in the work and areas purely of laboratories, analysis and results. The practice is intended to be a point of support in the technical, execution and administrative area, which implies better performance in the development of work activities that are carried out within the company such as planning of mining executions, adequate management plans of equipment, instruments or personnel in charge, periodic evaluations, monitoring of work carried out in mining exploration, drafting of essential documents for the initiation, development and completion of mining processes. In this way, support is essential for the verification and good management of both the company and the projects in charge; in order to obtain satisfactory results with each of the goals to be met.